Muslim Contributions to the Modern American Politics during Obama’s Presidency - غيلاني، سهى, غريسي، عبير (University of El-oued, 2022)
تبحث هذه المذكرة في موضوع مساهمة المسلمين في السياسة الأمريكية خلال فترة رئاسة باراك أوباما، وتناقش بشكل أساسي أنظمة الهجرة الأمريكية، الجماعات الدينية في الولايات المتحدة، ظهور الإسلام وأول المسلمين الذين يأتون إلى العالم الجديد، هيكل النظام السياسي الأمريكي، وعملية الانتخابات الرئاسية الأمريكية. وهي تقدم أيضا رئاسة باراك أوباما ، وتركز على مشاركة المسلمين في المجال السياسي الأمريكي خلال فترة حكم الرئيس السابق أوباما. الهدف الأساسي من هذا البحث هو التعرف على تأثير المسلمين على المجتمع الأمريكي بالإضافة إلى مشاركتهم في الإطار السياسي. يأتي هذا التحقيق للفت الانتباه لموضوع مساهمة المسلمين في السياسة الأمريكية، ويفتح أبواب المناقشات والمزيد من البحث في هذه القضية. تنتمي هذه الورقة البحثية إلى المنهج الوصفي التحليلي للبحث. تم التحقق من صحة هذه الفرضية باستخدام استبيان تم إرساله إلى مجموعة من المسلمين الذين يعيشون في الولايات المتحدة الأمريكية. تأتي مناقشة وتحليل نتائج أداة البحث هذه للتحقق من صحة الفرضية وإثبات أن المسلمين بالفعل يشاركون ويساهمون ويؤثرون وينخرطون في المجال السياسي الأمريكي بشكل عام وفي عهد باراك أوباما خاصة، بالإضافة إلى حصولهم على مناصب سياسية مهمة في الحكومات الأمريكية. This dissertation in hand investigates the topic of the contribution of Muslims to the American politics during Barack Obama's presidency, it discusses mainly, the American immigration system, religious groups in the United State, the emergence of Islam, and the first Muslims who come to the new world, the structure of the American political system, and the American process of the presidential election. It also gives an overview of Barack Obama's presidency and focuses on the participation of Muslims in the American political sphere pending Obama's rule. The fundamental objective of this research is to identify the influence of Muslims on American society as well as their participation in the political framework. This investigation comes to bring attention and significance to the topic of Muslims' contribution to American politics and opens doors to discussions and further research into this issue. This research paper belongs to the descriptive˗analytical approach of research. Checking the validity of this hypothesis is done using a questionnaire submitted to a group of Muslims who live in the United States of America. Discussion and analysis of the consequences of this research tool come to validate the hypothesis and prove that Muslims, indeed, participate(d), contribute(d), influence(d), and engage(d) in the American political field during Barack Obama's era, in addition to, their obtaining significant political positions in the American government
Keywords: السياسة الأمريكية، باراك أوباما، مساهمة المسلمين، النظام السياسي، الجماعات الدينية.; American politics, Barack Obama, Muslims' contribution, political system, religious groups.